THE UPDATED METHOD OF CONTROL OF GROUP OF QUADROCOPTERS - P. V. Samoilov; K. Y. Ganshin; O. S. Mezentseva; D. L. Vinokursky (Современная наука и инновации)
In this article, the method of swarm control was presented. To coordinate the group, the spatial trajectory of UAV has to be implemented by applying efficient control law. The principle of coordinated rotation has been introduced. The coordinated rotation allows receiving analytical equations of spatial motion which are represented within defining of the vector of velocity and yaw angle. The method was evaluated in Gazebo simulator. All results were utilized to move the group within the environment.